Demonstration Exam in Continuing Entrepreneurial Education within the VET and HE Systems - O. A. Romanova; K. V. Anisimova (Высшее образование в России)
Achieving the national development goals of the Russian Federation and maintaining the sustainability of the economy in the face of sanctions pressure impose special requirements on the development of entrepreneurial competencies among students of postsecondary education. One of the key innovations of the last decade in the field of entrepreneurial education in Russia was the introduction of a demonstration exam (DE) based on WorldSkills Russia methodology. Its results reveal high heterogeneity in the quality of entrepreneurial competencies acquisition among the students. Meanwhile, the experience of educational organizations that effectively cope with mass preparation for DE has not yet been sufficiently studied. Moreover, the specifics of the formation of entrepreneurial competencies in VET have not been studied, despite the steady growth in the share of college graduates in the university applicant base. In order to ensure the continuity of entrepreneurial education for students studying along the VET–HE trajectory, as well as to study the best practices for the formation of entrepreneurial competencies in the prism of DE, qualitative research of the search type was implemented.The study was carried out based on qualitative methodology. Within its framework, in-depth semi-structured interviews were conducted with expert teachers from four educational institutions with the highest results in the DE. For the triangulation? The data also included 4 in-depth semi-structured interviews with VET students who have successful experience in confirming the results of mastered entrepreneurial competencies. The interview analysis was based on a mixed approach.Structural and procedural components are identified and described, showing ways to integrate entrepreneurial education into traditional VET and to create a comprehensive educational environment. Interactive components used in teaching and learning entrepreneurship are investigated. According to the research results, as in the case of leading foreign practices, the best domestic practices are characterized by the use of constructivist pedagogy, while the key teaching method is long-term interdisciplinary student projects. The specificity of the formation of entrepreneurial competencies in VET has been revealed – this is a practice orientation and an orientation towards routine entrepreneurship.The results obtained can be used by practitioners to improve the quality of entrepreneurial education in VET schools.